Aggregate accounting information and its impact on management decision-making ( Case Study ) - Kdeear, Ahmed Yhia; Halim, Safwan Qusay Abdel (Journal of Economics and Administrative Sciences, 2021)
The main aim of this paper is to explain the effect of the aggregation accounting information on the financial, investment, and operational, managerial decision-making and the evaluation of the financial statements after aggregate. The problem of this study is represented in administrative decision-making that takes place under differentiated accounting systems operating within a governmental economic unit that seeks at the same time to achieve a unified vision and goals for the organization. This study was conducted at the College of Administration and Economics /University of Baghdad, and it represents a sample from a community of governmental economic units that apply differentiated accounting systems. The study method is represented by adopting the descriptive approach in showing the effect of aggregate accounting information on making and making administrative decisions based on scientific and rational methods. The study concluded the most important conclusions, which is that when aggregate the accounting information, the qualitative characteristics of the accounting information change and become more beneficial to the decision-maker, and a change occurs in the direction of the administrative decision inside and outside the governmental economic unit